174 Multi-enzyme solution improved growth performance of piglets fed a corn-SBM-DDGS based diet. (5th December 2019) - Perez, Victor G; Li, Wenting; Hong, Jinsu; Rudolph, Bryan; Souza, Ana Lucia Pozzobon de; Remus, Janet C; Woyengo, Tofuko A
Abstract: A study was conducted to determine the effect of adding a multi-enzyme product to corn-SBM-DDGS-based diet on growth performance of weaned pigs. A total of 132 pigs weaned at 21 d of age (initial BW=7.5±1.5kg) were blocked by weight and housed in pens of 4 barrows (6) or gilts (5) per pen (n = 11). The diets consisted of: 1) a corn-SBM-based diet with high animal-by products (Comp); 2) a corn-SBM-based diet with 5 to 15% DDGS and reduced animal-by products (Simp); and 3) Simp with a multi-enzyme product that supplied 4, 000 U of xylanase, 150 U of β-glucanase, 150 U of amylase and 3, 000 U of protease/kg (Simp+ENZ). All diets were isoenergetic and met the NRC (2012) recommendations for weaned pigs. The diets were fed for 6 weeks with a 3-phase-feeding program: phase-1, 0–7 d; phase-2, 7–21 d and phase-3, 21–42 d post-wean. A Buttiauxella spp. phytase was supplemented at 2000, 1250 and 1250 FTU/kg for phase-1, 2 and 3, respectively. Pharmaceutical level of Zn was only included in phase 1 and 2 at 3000 and 2000 ppm, respectively. Performance was measured by phase and analyzed using SAS MIXED model with repeated measure. Average ADG from 0–42 d was 521, 465 and 434 g/day in pigs fed Comp, Simp+ENZ and Simp diet, respectively (P < 0.05). The ADFI was 861, 765 and 778 from 0–42 d in pigs fed Comp, Simp and Simp+ENZ (P < 0.05). Final BW for pigs fed Simp+ENZ was 1.36 kg heavier than those fed Simp (26.93 vs. 25.57 kg, P < 0.05). Fecal score was not affected by feeding Simp diet with or without enzyme as compared to those fed Comp diets (P > 0.05). In conclusion, the multi-enzyme solution significantly improved ADG when piglets were fed a diet containing low animal by-products and high DDGS.